Influence of electrolyte on the zirconium electrolysis process for nuclear power engineering - Moravetsky, S.I.; Kasatkin, O.G.; Tsaryuk, A.K.; Kravets, V.P.; Goncharov, I.V.; Ivanko, A.V. (Вопросы атомной науки и техники, 2020)
The effect of welding method and technique on the HAZ microstructure in dissimilar welded joint of the type reactor vessel steel + deposited austenitic layer was investigated. The results of metallographic studies and bend tests of the welded joints are evidenced that the development of technology for weld repair of an anticorrosive coating with access to the base metal without subsequent high tempering is advisable on the basis of “buttered layer” technique by MMA welding with layer–by–layer controlled change in linear energy. This approach provides a uniform fine-grained microstructure at the overheat region of the HAZ. TIG welding with the filler wire and constant layer–by–layer linear energy also allows to refine overheat region microstructure. However, in this case, it is characterized by two types of structural heterogeneity caused by intense overheating of the base metal and diffusion of alloying elements and carbon. Досліджувався вплив способу зварювання на структуру металу зони термічного впливу (ЗТВ) у різнорідному зварному з’єднанні типу корпусна реакторна сталь + наплавлений аустенітний шар. Результати металографічних досліджень та випробувань на згин металу зварних з’єднань показали, що розробка технології ремонтної наплавки антикорозійного покриття з виходом в основний метал корпусу реактора без наступного його високого відпуску доцільна на основі техніки проміжного шару при зварюванні покритими електродами з пошаровою контрольованою зміною погонної енергії. Цей підхід забезпечує на ділянці перегріву ЗТВ однорідну дрібнозернисту структуру. Ручне аргонодугове зварювання з подачею присадки і пошарово незмінною погонною енергією також дозволяє подрібнити зерно на ділянці перегріву. Однак при цьому для неї є характерним два види структурної неоднорідності, пов’язані з інтенсивним перегрівом основного металу і дифузією легуючих елементів та вуглецю. Исследовалось влияние способа сварки на структуру металла зоны термического влияния (ЗТВ) в разнородном сварном соединении корпусная реакторная сталь + наплавленный аустенитный слой. Результаты металлографических исследований и испытаний на изгиб металла сварных соединений показали, что разработка технологии ремонтной наплавки антикоррозионного покрытия с выходом в основной металл корпуса реактора без последующего его высокого отпуска целесообразна на основе техники промежуточного слоя при сварке покрытыми электродами с послойным контролируемым изменением погонной энергии. Этот подход обеспечивает на участке перегрева однородную мелкозернистую структуру. Ручная аргонодуговая сварка с подачей присадки и послойно неизменной погонной энергией также позволяет измельчить зерно на участке перегрева. Однако при этом для него характерны два вида структурной неоднородности, связанные с интенсивным перегревом основного металла и диффузией легирующих элементов и углерода.